Alleviating adolescent stress, anxiety, and fear through music and sports games during the COVID-19 pandemic: A randomized controlled trial - Jiarun Wu; Garry Kuan; Abdulwali Sabo; Yee Cheng Kueh; Frank J.H. Lu (iScience)
Summary: This study assessed the effects of combining music with sports games on stress and anxiety relief in adolescents during the COVID-19 pandemic. Methods: In an 8-week randomized trial, 200 participants were divided into four groups: music-only, sports-only, combined music and sports, and a control group (traditional exercise). Stress (SAVE-6), anxiety (FCV-19), SpO2, and heart rate (HR) were measured before and after the intervention. (1) All groups reduced stress and anxiety (p < 0.05), with the combined group showing the greatest improvement (p < 0.05). (2) Sports and combined groups significantly reduced fear of COVID-19 (p < 0.05). (3) SpO2 improved most in the combined group (p < 0.05). (4) HR decreased significantly in sports and combined groups (p < 0.05). Combining music and sports games effectively reduces stress and anxiety while improving physiological health in adolescents.